Hotărârea Curții Europene a Drepturilor Omului în cauza S.C. Zorina Internațional S.R.L împotriva României - Loneta-Honorina Gavrea (Drepturile Omului)
The European Court of Justice, in case 15553/15, issued a ruling regarding the administrative sanctioning of a commercial company that violated national legislation regulating the obligation for economic operators to use electronic fiscal devices and the framework for implementing this obligation. The company failed to issue fiscal receipts for a small amount, for which the national legislation in force at that time prescribed cumulative and strict sanctions: a substantial fine and the suspension of the company’s activity for a period of three months. The referral to the Court regarding the contested interference fell within the scope of analysis of the second paragraph of Article 1 of Protocol 1 concerning measures “to regulate the use of property” and with regard to the fine “to ensure the payment of taxes or other contributions or fines”. The Court’s assessment of whether the national authorities ensured a fair balance between the general interest, on the one hand, and the respect for property rights, on the other hand, was made by a majority vote, six to one. It was concluded that there was no violation of Article 1 of Protocol No. 1 of the European Convention on Human Rights. However, the minority opinion opened a new perspective in the judicial approach to such cases, namely whether it is reasonable for the national legislation of the Convention’s signatory member states to impose excessive sanctions for the commission of a minor administrative offense, and what the limits of such an approach should be.